IFS Supplement on Monetary and Financial Statistics. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2006)
This paper presents the special quarterly supplement to the International Financial Statistics (IFS) 2006. The IMF is publishing the monetary statistics for those member countries that have commenced the reporting, on a regular basis, of monetary data that accord with the methodology in the IMF's Monetary and Financial Statistics Manual (MFSM), 2000. Exchange rates are expressed in time series of national currency units per SDR and national currency units per US dollar, or vice versa. An increase in the index reflects an appreciation. Because of certain data-related limitations, particularly where Fund estimates have been used, data users need to exercise considerable caution in interpreting movements in nominal and real effective exchange rates. Statistics on the accounts of financial corporations are given in sections 10 through 50 in the country tables. Data for the depository corporations and other financial corporations are consolidated into a Financial Corporations Survey.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet